Structural problems of the accreditation of higher education in Chile: 2006-2012 - Barroilhet, Agustín (Revista Pedagogía Universitaria y Didáctica del Derecho, 2019)
This article comprehensively examines the accreditation of higher education in Chile focusing on three aspects that determined its performance: (1) the initial market scenario, marked by hierarchies and segmentation among institutions, (2) the problems associated with accreditation’s design which allowed it to reflect these hierarchies, and (3) the problems arising from associating accreditation with public funding of loans for disadvantaged students while total enrollment was expanding through the underperforming institutions that enrolled these. The thesis is that these three factors conflated to turn accreditation into a sham system that was used to justify the distribution of the funding to which it was associated. The article ends providing some lessons for countries planning on importing or improving their accreditation systems.